Interprofessional collaboration in interdisciplinary healthcare teams - Šanc, Petra (Obzornik zdravstvene nege, 2022)
Introduction: With the introduction of new concepts of work culture and contemporary forms of collaboration in interdisciplinary teams, inter-complementarity and understanding of the skills of each professional group have become indicators of successful interprofessional collaboration. The aim of this study was to identify the characteristics of the process of interprofessional collaboration in healthcare teams, as well as to pinpoint the key components of effective collaboration. Methods: In this non-experimental quantitative study, we used a modified Interprofessional Collaboration Scale in order to assess interprofessional collaboration in interdisciplinary teams. Our random sample included 203 healthcare professionals. Of these, 147 (72.4%) were nurses, 27 (13.3%) were doctors and 29 (14.3%) were other healthcare professionals. Data were analysed using basic descriptive statistics, correlation coefficient (Spearman correlation), Kolmogorov-Smirnov and Shapiro-Wilk tests and Mann-Whitney U test. Results: The results show statistically significant differences in the level of satisfaction between individual health profiles. On average, doctors rated their collaboration with nurses most positively (x = 3.03, s = 0.26) and were also satisfied with their collaboration with other healthcare professionals (x = 2.86, s = 0.22). Nurses rated their collaboration with doctors least favourably (x = 2.36, s = 0.42). Discussion and conclusion: The results provide information on the evaluation of the current level of collaboration in interdisciplinary teams, with doctors rating this collaboration more positively and nurses being more critical in their assessment. The differences in the views and attitudes of healthcare professionals regarding the importance of collaboration indicate that there is a need for changes in formal education in the field of interprofessional collaboration.
Keywords: komunikacija; medsebojna razmerja; medsebojni odnosi; timsko delo; zdravstveni delavci